Peran Sistem Pengendalian Internal dalam Efisiensi Biaya Operasional pada Joglo Gym - Rizki Miftah; Enik Rahayu (Mahesa Research Center, 2026)
This article aims to analyze the role of internal control systems in supporting operational cost efficiency at Joglo Gym Bergas, Semarang Regency. The problem focuses on how internal control systems are implemented in a local-scale fitness service business and their role in controlling and improving operational cost efficiency. To address this issue, the study adopts theoretical perspectives on internal control systems and operational cost efficiency within the context of small and medium-sized enterprises. Data were collected through in-depth interviews with the owner and manager, direct observation of operational activities, and simple documentation related to cost records, and were analyzed qualitatively using a case study approach. The findings indicate that the internal control system is implemented informally through task division, direct supervision, and centralized decision-making on expenditures, and plays a role in improving efficiency in electricity costs, equipment maintenance, and labor management without reducing service quality. The novelty of this study lies in the finding that informal internal control systems based on daily managerial practices remain effective in promoting cost efficiency in local-scale fitness service businesses. This study contributes theoretically by expanding the understanding that the effectiveness of internal control systems is not solely determined by their level of formality, but also by the consistency of implementation and their alignment with the business context.